Samtidskunst, repræsentation og remediering - Exe Christoffersen, Erik (Peripeti, 2022)
Samtidskunst, repræsentation og remediering by Erik Exe Christoffersen. Christoffersen emphasizes FIX&FOXY’s way of doing remediation, perceived as a way of ‘overpainting’ a work like a palimpsest.